(untitled) (KULT_online, 2025)
In Das Deutsche Demokratische Reich, Volker Weiß analyzes strategies of far right’s resignifications in the field of history in the German, Russian, and U.S. Weiß focuses on Russian history politics and its European ties; the right’s ‘Eastern dilemma’ between Eurasian fantasies and anti-Slavic tradition; the myth that National Socialism as a left-wing movement, and an ‘anti-communist GDR nostalgia’ as an anti-liberal counter-identity. The result is a substantive study of the practices of historical reinterpretation, demonstrated through tightly argued case studies.